(NdAWNQ (Bi (NSEREDNXOW(Bi(N^NA (Bi(NSTOR(Bi(NQ uKRA)QÇNI (B:s)E (NNAW^ALXNIJ POS(Bi(NBNIK (B/s - (NwINOKUR(B, I.,s ((NkI)QÇW (B:s)E (NgLOBUS(B,s, 1996)
(NkNIGA PRISWQ^ENA DAWN)QÆJ TA SEREDNXOWÆ^NÆJ ÆSTORÆÇ uKRAÇNIs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: )Qæ(NSTORÆQs)E -- (NuKRA)QÇNAs)E; (NMISLIWC(Bis; (NDAWNQ )QÆSTORÆQs)E; (NSEREDNXOW)QÆ^NA ÆSTORÆQs)E; (Np)QÆWNÆ^NE pRI^ORNOMOR(B'(NQs)E; (NRIBALKIs; (NZEMLEROBIs; (NSKOTAR(Bis; (NK(Bi(NMMER(Bi(NJSXKIJs; (NSARMATSXKIJ ^ASs; (NSK(Bi(NFIs; (NGRECXK(Bi (NM(Bi(NSTAs; (NSH(Bi(NDN(Bi (NSLOW(B`(NQNIs; (NkI)QÇWSXKA rUSXs)E; (NrUSX(B-(NuKRA)QÇNAs)E